Richness, use and origin of expended medicinal plants in the markets of the Cusco City - Huamantupa, Isau (2011)
We studied medicinal plants expended in five major markets, San Pedro, San Jerónimo, Ttio, Wanchaq and four small zonal, Rosaspata, San Sebastian, Molino II, Huancaro and Santa Rosa, in the city of Cusco. It was aimed to know the richness, how to use treated conditions, place of origin, distributions and source. We recorded 152 species into 45 families, the families more riches were Asteraceae with 36 species and Lamiaceae (12), species most frequently bought and sold in all markets were Muehlenbeckia volcanica (Benth.) Endl. "Mullaca" Perezia virens (D. Don) Hook. & Arn. "Valeriana", Matricaria recutita L. "Manzanilla" and Hypochaeris taraxacoides (Walp.) B. & H. "Pilli pilli", the herbaceous habit represent 75%,the total of the parts used, 81% correspond to the entire plant, the infusions or "mates calientes" with 69% of the mode of preparation and conditions treated most frequently were the bronchopulmonary, kidney and inflammations, liver and gastrointestinal ailments. Native species accounted for 83% of the total, these 78% are from the Andean region surrounding towns mainly Cusco department. We believe that this great wealth of medicinal plants expended in the markets of the city of Cusco is similar to other important records in Andean South American markets such as Bolivia and Ecuador, which in turn are rooted in ancient knowledge, mainly Quechua culture.